Neutron Compton scattering investigation of sodium hydride: from bulk material to encapsulated nanoparticulates in amorphous silica gel. - Seel, A; Sartbaeva, A; Mayers, J; Ramirez-Cuesta, A; Edwards, P (2011)
In this study we utilize neutron Compton scattering (NCS) to determine differences in nuclear momentum distributions in NaH, both as bulk material and encapsulated as nanoscale particles (from 20 to 50 nm in diameter) within an amorphous silica-gel matrix (SiGNaH). In addition, elemental Na dispersed in such a matrix is also studied (SiGNa). Data treatment and fitting of experimental spectra yields comparison of the nuclear Compton profiles and radial momentum distributions for the proton in both bulk NaH and nanoscale SiGNaH, with resultant proton kinetic energies being in agreement with previous inelastic neutron studies of bulk NaH. Slight differences in proton radial momentum distributions for bulk and nanoscale systems are witnessed and discussed. The technique of stoichiometric-fixing is applied to the backscattering spectra of each system in order to examine changes in the Na profile width, and NCS is shown to be sensitive to the chemical environment change of this heavier nucleus. Examination of the Si and O profile widths in the gel samples also supports this method.